PROFIL PENGGUNAAN ANALGETIKA PADA PASIEN NYERI AKUT PASCA BEDAH DI RSUP SANGLAH BULAN SEPTEMBER TAHUN 2013 - Saputra, Ida Bagus Alit; Suarjaya, I Putu Pramana; Wiryana, I Made (E-Jurnal Medika Udayana; vol 5 no 2(2016):e-jurnal medika udayana, 2016)
ANALGESICS USING PROFILE TO THE PATIENTS WITH POST-SURGERY ACUTE PAIN IN SANGLAH GENERAL HOSPITAL, SEPTEMBER 2013 Surgery is a common action taken to overcome the problem of patients who got tissue-damagewhich caused the pain. Acute pain of patients which is happened after the surgery generally accompanied by emotional and autonomic response that inflicted physiological response and finally would disturb the patient’s recovery process. The pain management usually uses multimodality analgesics such as opioid group, NSAID (Non Steroid Anti-Inflammatory Drugs), and adjuvant. Many patients still complaining because of the pain management therapy has not run well yet. This complained caused by the less knowledge or understanding of the medical practitioner about analgesics regiments, which made they are still afraid of the side effect that may affect patients.  This research is aim to acknowledge the pain overcoming profile and analgesics therapy method in Sanglah General Hospital to the post-surgery patients during September 2013 and characteristic of the post-surgery patients. The design of this research is non-experimental cross-sectional which gathering data retrospectively using the secondary data of APS (Acute Pain Service) that belongs to Anesthetic, Re-animation, and Intensive Care Department of Sanglah General Hospital during September 2013, which amount 396 samples.Result and conclusion of this research is from 396 after surgery patients during September 2013 in Sanglah General Hospital receive multimodality analgesics regiments with 5 therapy method and monitoring by VAS (Visual Analogue Scale). Characteristics of patients with male sex amounts to 206 (52.0%) with the status ASA (American Society of Anesthesiology) dominated ASA 1 shows a patient undergoing surgery in good condition without significant systemic disorders. There are 13 types of surgeries which the largest number is 72 cases (18.2%).  There are 154 persons of the sample (38.9%) receive the therapy method using syringe pump which become the most frequently method used to overcome the acute pain happened post-surgery. The pain measurement 24–48 hours reduced in amount 2.7 point which is calculated using VAS (Visual Analogue Scale).
Keywords: Post-surgery acute pain, VAS, Analgesics